Digital Banking Transformation AI Enhances Efficiency And Customer Experience Seminar Perspective Industry - Dede Arisko Agustiawan (Universitas Prof. Dr. Moestopo (Beragama), 2024)
This study examines the transformative impact of artificial intelligence (AI) on operational efficiency in the Indonesian banking sector. It investigates how AI technologies enhance responsiveness to customer inquiries, streamline service processes, and improve overall customer satisfaction. Using a qualitative approach, the research integrates literature reviews, in-depth interviews, and case studies to comprehensively analyze AI adoption and its implications. The findings demonstrate that AI implementation not only boosts operational efficiency but also facilitates personalized customer service through advanced data analytics and AI-driven automation. The study emphasizes the importance of transparent AI algorithms and robust data protection measures to address ethical considerations and ensure adherence to Sharia principles. Insights from leading banks such as Bank Mandiri and Bank BRI highlight substantial reductions in operational costs and enhanced service capabilities following AI integration. This research contributes to a deeper understanding of AI's role in shaping contemporary banking services and provides strategic recommendations for optimizing AI applications in Indonesian banks.